Optimal pricing for new and remanufactured products - Abbey, James D.; Blackburn, Joseph D.; Guide, V. Daniel R. (Journal of Operations Management, 2015)
AbstractThis work investigates the optimal pricing of new and remanufactured products using a model of consumer preferences based on extensive experimentation. The experimental investigation reveals two distinct segments of consumers. One segment is relatively indifferent between new and remanufactured products and displays high sensitivity to price discounts. The second segment shows strong preferences for new products—with an accompanying aversion to remanufactured products—and realtively low sensitivity to price discounts. The pricing analysis examines several scenarios involving a new product manufacturer, ranging from a simple monopolist scenario to a more complex scenario involving competition with third‐party remanufacturers. In contrast to the usual finding that new product prices should decrease when competitive remanufactured products enter the market, the introduction of market segments reveals a robust finding across all scenarios: when remanufactured products enter the market, the optimal price of the new product should increase. Through appropriate pricing of new products, the OEM can mitigate the effects of cannibalization and increase profitability.